Onset and persistence of efficacy by symptom domain with long-acting injectable paliperidone palmitate in patients with schizophrenia. (May 2014) - Alphs, Larry; Bossie, Cynthia A; Fu, Dong-Jing; Ma, Yi-Wen; Kern Sliwa, Jennifer
<x xml:space="preserve">Abstract</x> Introduction: Several long-acting injectable (LAI) second-generation antipsychotics are now available for the management of schizophrenia. As patients with schizophrenia frequently present with diverse and challenging symptoms, it is important to understand the effects of antipsychotics in treating these different symptom subgroups and the timing of these responses. Areas covered: For this review, data from two randomized, double-blind trials were analyzed in respect to the onset and persistence of effects on several measures of psychopathology (as measured by the Positive and Negative Syndrome Scale [PANSS]) after treatment with LAI <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=paliperidone palmitate&logicalOpe1=OR&field2=articletitle&text2=paliperidone palmitate&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">paliperidone palmitate (PP) (NCT00590577 and NCT00589914). Expert opinion: Symptom reductions from baseline with PP were significant by day 4 for all five PANSS factors in both studies. Some effects may have been driven by the presence or absence of a placebo response. A significant effect for PP versus placebo was observed for all major symptom domains for one or more doses of PP during the first month of treatment. Once established, most (but not all) significant responses persisted to the end point. Similar improvements were observed in PANSS scores with PP and oral risperidone. Dose-dependent trends were observed for the effect of PP on positive, negative and uncontrolled hostility/excitement symptoms.